Changing our perspective: Is there a government obligation to promote autonomy through the provision of public prenatal screening?. (6th July 2020) - Enzo, Aya; Okita, Taketoshi; Asai, Atsushi
Abstract: In many countries, prenatal testing for certain fetal abnormalities is offered via publicly funded screening programs. The concept of reproductive autonomy is regarded as providing a justificatory basis for many such programs. The purpose of this study is to re‐examine the normative basis of public prenatal screening for fetal abnormalities by changing our perspective from that of autonomy to obligation. After clarifying the understanding of autonomy adopted in the justification for public prenatal screening programs, we identify two problems concerning this justification: first, the extent to which the government is obliged to meet this demand is not evident; and, second, it is not clear whether the provision of public screening is the most appropriate way to promote autonomy. Next, to tackle these problems, we focus on Onora O'Neill's argument of rights and obligations. Drawing on this argument, we show that, in addressing the problems above, it is important to change our normative perspective from rights or autonomy to obligation. Our argument will show that since the government does not have an incontrovertibly fundamental obligation to promote autonomy, this obligation needs to be constrained in terms of compatibility with other fundamental obligations. In addition, even if a government is obliged to promote autonomy to some degree, there could be more appropriate means to achieve it than providing public prenatal screening; therefore, it is not necessary for government obligations to extend to the provision of public prenatal screening.